Bomb vessels - Pearsall, A. W. H. (Polar Record, 1973)
Readers may wonder why such warlike-sounding ships should intrude into the pages of a journal that is devoted to the study of regions where we must hope that war will always be excluded. It will be seen, however, that many of the vessels that contributed to the exploration of both the Arctic and the Antarctic were drawn from a type of ship denominated “bomb vessel” or merely “bomb” for short (see Table 1). Their “fiery” or “explosive” names still appear on the map, and several of them had distinguished careers. Some account of these interesting ships may provide a useful background to polar studies.